Localized induction heating of metallic spacers for energy-efficient membrane distillation - Tan, Yong Zen (2022)
Despite membrane distillation (MD) being well acknowledged as a green technology for water treatment, it remains unattractive for commercial implementation due to limited energy efficiency, and temporal fluctuations in sustainable energy sources like waste heat and solar. The induction heating of metallic spacers addresses these shortcomings. In this study, we harnessed the high thermal conductivity of nickel (Ni) spacers and their capacity to be inductively heated to improve the energy efficiency of direct contact MD, and benchmarked the performance against the conventional external heating of the bulk feed and the use of polypropylene (PP) spacers. Both simulations and experiments were performed. Noteworthy results include: (i) induction heating gave higher flux and energy efficiency than the conventional external heating and use of PP mesh, particularly at lower flowrates; and (ii) induction heating was able to supplement external heating without a decrease in energy efficiency, which makes it a promising method to circumvent the problem of temporal fluctuations of waste or solar heat. This study demonstrated the feasibility of localized induction heating of metallic spacers in MD, which has potential for further improvements through optimizations of the thermal conductivity and geometry of the spacer, and energy efficiency of the induction heater.